Effect and mechanism of Huangkui capsule inhibiting oxidative stress and fibrosis indicators in patients with diabetic nephropathy with stage Ⅲ-Ⅳ - XU Ji-yao; ZHANG Yu; ZENG Qiao (Linchuang shenzangbing zazhi)
Objective To study the effect of Huangkui capsule inhibiting oxidative stress and fibrosis index in patients with diabetic kidney disease(DKD)with stageⅢ-Ⅳ,so as to explore the mechanism of Huangkui capsule in the treatment of DKD.Methods 100 patients with DKD with stageⅢ-Ⅳfrom June 2014 to October 2015 were randomly divided into two groups,50 in each group.The patients in the control group were given conventional treatment,and those in the treatment group additionally received Huangkui capsule orally,5 capsules each time,3 times every day for 6 months.The kidney function,and urine and serum levels of oxidative stress and fibrosis indicators were detected.Results The SCr,BUN,andβ2-MG levels in two groups after treatment decreased,CCr increased,and there was statistically significant significance between two groups(P <0.05).The UAER and 24-h urine proteinin two groups after treatment were significantly lower than those before treatment,and those in the treatment group were significantly lower than those in the control group(P<0.05 for all).The MDA and MPO concentrations intwo groups after treatment were significantly lower than before treatment,SOD activity was significantly higher than before treatment,and there was statistically significant difference between two groups(P<0.05).There was no statistically significant difference in 8-OHdG in two groups before and after treatment(P>0.05).The serum IV-C,PC Ⅲ,LN and HA levels after treatment in two groups were significantly lower than before treatment,and those in study group were significantly lower than those in the control group(P<0.05 for all).Conclusions Huangkui capsule can antagonize the oxidative stress injury in kidney tissues probably by influencing the release of fibrosis factor and improving the renal fibrosis.